Molecular and biochemical characterization of CTX-M-131, a natural Asp240Gly variant derived from CTX-M-2, produced by a Providencia rettgeri clinical strain in São Paulo, Brazil - Dropa, Milena (2015)
CTX-M-131 is a natural Asp240Gly variant from the CTX-M-2 group detected in a Providencia rettgeri clinical strain from Brazil. Molecular analysis showed that blaCTX-M-131 was inserted in a complex class 1 integron harbored by a 112-kb plasmid, which has not been previously described as a platform for CTX-M-encoding genes with the Asp240Gly mutation. Steady-state kinetic parameters showed that the enzyme has a typical cefotaximase catalytic profile and an enhanced activity against ceftazidime.